Wernicke’s encephalopathy in a patient with non- Hodgkin’s lymphoma post-Autologous HSCT - Leitão, João Paulo de Vasconcelos (2018)
Wernick’s Encephalopathy (WE) is an acute neuropsychiatric syndrome caused by thiamine deficiency post hematopoietic stem cell transplant (HSCT). WE is associated with high mortality and morbidity rates, but due to its rare occurrence, it is rarely considered in patients submitted to this procedure. Considering that, the manuscript reports the clinical characteristics and the possible factors that predisposed the occurrence of WE in a patient with non-Hodgkin’s lymphoma post-Autologous HSCT. We conclude that WE should be considered in patients submitted to autologous HSCT associated with prolonged use of TPN and malnutrition.